Survey of obstetricians' approach to the issue of reinfibulation after childbirth in women with prior female genital mutilationAJOG MFM at a Glance - Aliya Naz, MRCOG; Stephen W. Lindow, FRCOG, FCOG (SA) (Elsevier, 2021)
BACKGROUND: The procedure of reinfibulation is the resuturing (usually after vaginal childbirth) of the incised scar tissue in women with previous female genital mutilation. Many authorities do not recommend the practice of reinfibulation. OBJECTIVE: We sought to assess physicians' approach to the practice of reinfibulation. STUDY DESIGN: A structured online, anonymous questionnaire was sent to 130 practicing obstetricians and gynecologists through Survey Monkey. RESULTS: The questionnaire was completed by 98 respondents (75.4%).This survey showed that 76% of obstetricians (74 of 98) agree with a standard policy of not performing reinfibulation. However, 37% of those who refused to perform reinfibulation (27 of 74) would agree to undertake it if the woman insisted because she feared marital problems or divorce, and 73% of them (54 of 74) would offer treatment from an obstetrician with a different view. CONCLUSION: The complex nature of reinfibulation is discussed and an alternative approach is suggested.